2018
DOI: 10.21873/anticanres.12992
|View full text |Cite
|
Sign up to set email alerts
|

Evodiamine Suppresses Survival, Proliferation, Migration and Epithelial–Mesenchymal Transition of Thyroid Carcinoma Cells

Abstract: Background/Aim: The aim of this study was to evaluate the effect of evodiamine alone or in combination with chemotherapeutic agents on thyroid carcinoma cells. Materials and Methods: TPC-1 and SW1736 thyroid carcinoma cells were used. Cell viability, cytotoxic activity, apoptosis and migration were examined by applying appropriate methods. Drug combination analysis was performed. Results: Evodiamine treatment of cells decreased cell viability, and Bcl2 and phospho-AKT protein levels. Cytotoxic activity and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…It has also reported that EVO can influence serotonin reuptake in the brain (11). In previous years, there have been multiple publications focusing on various aspects of EVO, in terms of its effects on proliferation, apoptosis and autophagy (12)(13)(14). As the main component of the Chinese medicine formulation Evodia (15), EVO has inhibitory effects on cervical, lung, colon and nasopharyngeal cancer and other tumor types, likely mediated by the inhibition of tumor proliferation, metastasis and angiogenesis and the promotion of tumor cell apoptosis and autophagy (16).…”
Section: Introductionmentioning
confidence: 99%
“…It has also reported that EVO can influence serotonin reuptake in the brain (11). In previous years, there have been multiple publications focusing on various aspects of EVO, in terms of its effects on proliferation, apoptosis and autophagy (12)(13)(14). As the main component of the Chinese medicine formulation Evodia (15), EVO has inhibitory effects on cervical, lung, colon and nasopharyngeal cancer and other tumor types, likely mediated by the inhibition of tumor proliferation, metastasis and angiogenesis and the promotion of tumor cell apoptosis and autophagy (16).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, EVO suppresses cancer growing by eliminating stemness and inhibiting invasion and migration (7,31). This is mainly due to the downregulation of epithelial-mesenchymal transition (EMT) (32)(33)(34). For instance, EVO elevated epithelial marker E-cadherin and reduced the expression of mesenchymal markers N-cadherin and vimentin (33), as well as matrix metalloproteinase-2 (MMP-2) and matrix metalloproteinase-9 (MMP-9) protein levels (32).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, EVO enhanced the efficacy of radiation therapy by significantly inhibiting the cell cycle progression and growth in human gastric cancer BGC-823 cells in vitro and markedly suppressing the tumor growth of BGC-823 xenografts in vivo , and the anticancer effect of EVO was related to the downregulation of the Her2/AkT/Bcl-2 signaling pathway (Hu C. et al, 2016). Furthermore, EVO alone or in combination with chemotherapeutic agent wortmannin could inhibit cell growth, migration, and EMT and induce apoptosis by decreasing the levels of Bcl-2, phospho-Akt, and matrix metalloproteinases-2 and -9 proteins and increasing the levels of p21 and p53 proteins in thyroid cancer TPC-1 and SW1736 cells (Kim et al, 2018). EVO could also inhibit cell growth, induce apoptosis and cell arrest via increasing the levels of phosphorylated Bcl-2 protein, ER stress protein, and protein kinase RNA-like ER kinase in human renal cancer A498 cells in vitro , and suppress the growth of A498 tumors in vivo (Wu et al, 2016).…”
Section: Anticancer Tcms Through Targeting Multiple Apoptotic Pathwaysmentioning
confidence: 99%